2001
DOI: 10.1002/1521-3951(200111)228:2<571::aid-pssb571>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Group-III Nitrides Hot Electron Effects in Moderate Electric Fields

Abstract: We studied the distribution function and basic characteristics of hot electrons in InN, GaN and AlN under moderate electric fields, and found that in relatively low fields (of the order of kV/cm) the optical phonon emission dominates the electron kinetics. This strongly inelastic process gives rise to a spindle-shaped distribution function and an extended portion of quasi-saturation of the current-voltage characteristics (the streaming-like regime). We prove that this hot electron regime holds for all three ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…This opens prospects for realization of the streaming regime and its applications at or above the nitrogen temperature. Indeed, recent studies 6,7 have shown that in bulk III-N materials, a strongly anisotropic electron distribution can occur, and the pronounced OPTT resonance as well as the THz generation can be achieved at moderate electric fields.…”
mentioning
confidence: 99%
“…This opens prospects for realization of the streaming regime and its applications at or above the nitrogen temperature. Indeed, recent studies 6,7 have shown that in bulk III-N materials, a strongly anisotropic electron distribution can occur, and the pronounced OPTT resonance as well as the THz generation can be achieved at moderate electric fields.…”
mentioning
confidence: 99%
“…(15), which depends only on the nonparabolicity parameter c . Mathematically, of special note is the very simple form of Eq.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15] Two main approaches were undertaken. [6][7][8][9][10][11][12][13][14][15] Two main approaches were undertaken.…”
Section: Introductionmentioning
confidence: 99%